Pengaruh Work-Life Balance dan Burnout Terhadap Produktivitas Karyawan: Tinjauan Literatur - Aulia Asy-Syifa, Ghina; Hayina Zahra, Maisya; Khairunnisa Amalia, Rahma; Dwi Agustien, Salsha; Parihah Nurasiah, Sofa (Teewan Journal Solutions, 2026)
This literature review aims to integrate, analyze, and evaluate previous literature regarding the effects of work-life balance and burnout on employee productivity and performance amidst the dynamics of the modern workplace. Utilizing a literature review method, this study selected and analyzed 11 scientific articles published between 2017 and 2025 sourced from the Google Scholar database. The synthesis of the literature reveals that work-life balance consistently exerts a positive and significant impact on employee productivity and performance, both directly and indirectly through mediating variables such as work motivation, job satisfaction, and work engagement. Conversely, burnout generally serves as a negative predictor of employee outcomes, though its statistical significance is highly contingent upon industry characteristics, workload structures, and demographic vulnerabilities, particularly among Generation Z employees. Practically, this review recommends that management design flexible and adaptive human resource management policies such as proportional workload distribution and psychological well-being support by considering the specific industry context and employee demographic profiles to sustainably optimize labor productivity